Meteorological Factors and the COVID-19 Pandemic: The Backdrop of Pakistan - Riaz, Muhammad; Akhtar, Muhammad Nadeem; Jinghong, Shu; Gul, Habib (Frontiers in Psychology, 2021)
Coronavirus victims are confirmed all around the world and millions of people are being put into self-isolation. In this backdrop, a superior appreciation of the effective parameters in epidemic spreading can cause a cogent assessment toward COVID-19. In this vein, the consequences of weather indicators on spreading of COVID-19 can play an instrumental role in current coronavirus situation enveloping the world. These elements entail time, maximum and minimum temperature, humidity, wind speed, and rainfall. By such incorporation, their consequent effects on coronavirus lay out in Pakistan are explored. In the current study, principal elements are considered including the number of infected patients with coronavirus in Pakistan. Autoregressive Distribution Lag (ARDL) approach is used for analyzing the effects and relationships of variables with the COIVD-19 expansion rate extracting data from, April 1, 2020 through April 30, 2021. The results revealed that maximum and minimum temperature, humidity, wind speed, and rainfall had a direct positive significant correlation with total and confirmed cases of the COIVD-19. Lastly, this brief communication escorts to clarify on the outbreak of coronavirus in the region.